Pengaruh Pendekatan Solution Focused Brief Counseling Untuk Meningkatkan Konsep Diri Akademik Siswa Di Sma Negeri 1 Tinambung Polewali Mandar - Nurfajriani Tahir; Farida Aryani; Abdullah Sinring; Mirdan, Moh (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2024)
The purpose of this study was to determine 1) Overview of students' academic self-concept 2) Overview of SFBC implementation 3) The effect of SFBC Counseling to improve academic self-concept in students. This research uses a quantitative approach with a Quasi experimental design model. The experimental design used is nonequivalent control group design. The population of this study was class XI students as many as 107 students and the research sample was 22 students who were divided into experimental groups and control groups, each of which amounted to 11 students. Sample withdrawal using proportional random sampling   technique.   Data   collection   using   academic   self-concept   scale instruments and observation guidelines. Data analysis used descriptive statistical analysis and parametric analysis, namely the t test. The results showed that: 1) The level of students' academic self-concept at pretest in the experimental and control groups was in the low category. At the time of the posttest, the level of academic  self-concept  of  experimental  group  students  changed  to  the  high category and in the control group remained in the low category 2) The implementation of Solution Focused Brief Counseling (SFBC) counseling is carried out in accordance with procedures that have been designed through stages, namely rational treatment, describing problems, developing clear goals, exclusion questions, developing solutions (solution building conversation), providing feedback (summary feedback) and using a rating scale and evaluation At the time of SFBC counseling implementation, student participation was in the high category. 3) There is a difference in the level of academic self-concept in the group that is given treatment and in the group that is not given treatment in the form of SFBC counseling. This means that the application of SFBC counseling has an effect in significantly improving students' academic self-concept at SMA Negeri 1 Tinambung.